Magnetic Fe3O4 composite bismuth oxyhalide photocatalytic material as well as preparation method and application thereof

By loading iodine elements in Fe3O4 and bismuth oxyhalide, magnetic Fe3O4/BiOIxCly composite photocatalysts are prepared, which solves the problems of low visible light absorption and poor catalytic activity of existing photocatalysts, achieving efficient and low-cost photocatalytic effects, and supporting the recycling and utilization of materials.

CN119819331APending Publication Date: 2025-04-15SHANGHAI SECOND POLYTECHNIC UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510309371.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-17
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing photocatalysts have low absorption rate of visible light, poor catalytic activity, and high energy consumption in the preparation process, and are difficult to recover and reuse.

Method used

Magnetic Fe3O4 composite bismuth oxyhalide photocatalytic material is used to load iodine elements into Fe3O4 and bismuth oxyhalide by co-precipitation method to form Fe3O4/BiOIxCly binary composite material, which improves its absorption capacity and catalytic activity to visible light.

Benefits of technology

Efficient absorption of visible light is achieved, catalytic activity is significantly improved, preparation cost and energy consumption is reduced, and the material is easy to be recycled and reused.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819331A_ABST
    Figure CN119819331A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of catalytic materials, and particularly relates to a magnetic Fe3O4 composite bismuth oxyhalide photocatalytic material and a preparation method and application thereof.The preparation method comprises the following steps that S1, bismuth nitrate pentahydrate and nitric acid are mixed in a container; s2, after bismuth nitrate is dissolved, potassium iodide, sodium chloride and sodium dodecyl sulfate are added, and then nanoscale Fe3O4 is added; s3, the container is placed in a constant-temperature water bath and stirred, ammonia water and deionized water are added after stirring, a mixture is obtained, faint yellow or orange precipitate gradually appears in the bottle, and the mixture is stirred and subjected to a reaction; and S4, after the reaction is finished, cooling to normal temperature, removing supernate in the container through magnetic separation to obtain a precipitate, and washing and drying the precipitate to obtain the Fe3O4 / BiOIxCly binary composite visible-light-driven photocatalyst, the preparation method is short in period, visible light can be strongly absorbed, and the activity of the catalyst under visible light irradiation is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalytic materials, and in particular relates to a magnetic Fe3O4 composite bismuth oxyhalide photocatalytic material and a preparation method and application thereof. Background Art

[0002] Although existing photocatalysts have certain effects, they have obvious shortcomings: first, most of them can only absorb ultraviolet rays, while sunlight contains more visible light, resulting in low light utilization of the materials; second, the electrons and holes (which can be understood as "energy carriers") generated by these materials under light are easy to recombine and become ineffective before they have time to participate in the reaction, resulting in poor catalytic activity. Although some people have tried to improve them by mixing other materials or high-temperature processing, these methods often require long-term high-temperature heating, which is costly and energy-intensive, and the improved materials are still difficult to recycle and reuse. Therefore, the development of a new catalyst that is low-cost, easy to prepare, can efficiently utilize visible light, and is easy to recycle has become an urgent problem that needs to be solved. Summary of the invention

[0003] The invention discloses a magnetic Fe3O4 composite bismuth oxyhalide photocatalytic material and a preparation method and application thereof, which mainly solve the problems of low visible light absorption rate and low activity of current photocatalytic materials.

[0004] To achieve the above object, the present invention provides a method for preparing a magnetic Fe3O4 composite bismuth oxyhalide photocatalytic material, comprising the following steps: S1. Mixing bismuth nitrate pentahydrate and nitric acid in a container; S2, after the bismuth nitrate is dissolved, potassium iodide, sodium chloride and sodium dodecyl sulfate are added, and then nano-sized Fe3O4 is added; S3, placing the container in a constant temperature water bath and stirring, adding ammonia water and deionized water after stirring to obtain a mixture, and gradually showing a light yellow or orange precipitate in the bottle, stirring the mixture and reacting; S4. After the reaction is completed, the mixture is cooled to room temperature, the supernatant in the container is removed by magnetic separation, and a precipitate is obtained. The precipitate is washed and dried to obtain Fe3O4 / BiOI x Cl y Binary composite visible light photocatalyst.

[0005] Furthermore, the molar mass of the bismuth nitrate pentahydrate is 10 mmol to 12 mmol.

[0006] Furthermore, the concentration of the nitric acid is 4 mol / L to 6 mol / L, and the volume is 20 mL to 22 mL.

[0007] Furthermore, the mass of the potassium iodide is 1.660 g to 1.760 g, the mass of the sodium chloride is 0.585 g to 2.925 g, and the molar mass of the sodium dodecyl sulfate is 40 mmol to 42 mmol.

[0008] Furthermore, the temperature of the constant temperature water bath is 85°C to 87°C, and the stirring time is 10min to 12min.

[0009] Furthermore, the volume of the aqueous ammonia is 20 mL to 22 mL, and the volume of the deionized water is 40 mL to 42 mL.

[0010] Furthermore, the precipitate was washed with deionized water and ethanol for multiple times.

[0011] Furthermore, Fe3O4 / BiOI x Cl y The molar ratio of iodine to chlorine in the binary composite visible light catalyst is 1:1-5.

[0012] The invention also provides a magnetic Fe3O4 composite bismuth oxyhalide photocatalytic material prepared by the preparation method.

[0013] The present invention also provides an application of the magnetic Fe3O4 composite bismuth oxyhalide photocatalytic material in TC degradation.

[0014] The technical solution provided by the present invention has at least the following technical effects: (1) The present invention prepares Fe3O4 / BiOI x Cl y The binary composite visible light catalyst, in which the ratio of iodine to chlorine is adjustable, has a short preparation cycle, low reaction temperature, low production cost, and energy saving. Due to the addition of iodine, the absorption wavelength of the composite material is red-shifted from the sunlight band (≥290 nm) to the visible light band (≥420 nm), which can produce strong absorption of visible light.

[0015] (2) Due to the interaction between Fe3O4 and BiOI x Cl y A semiconductor heterojunction is formed between the two, which accelerates the separation of photogenerated electrons and holes, effectively inhibits their recombination, and greatly improves the activity of the catalyst under visible light irradiation.

[0016] (3) When the iodine:chlorine ratio is 1:2, under the irradiation of visible light, the degradation rate of 10 mg / L tetracycline (TC) solution reaches 92.3% in 60 min. The catalyst can be recycled and reused by applying an external magnetic field. After the catalyst is reused for 3 times, the degradation rate of TC is still higher than 85%. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0018] Figure 1 The Fe3O4 / BiOI 1 / 3 Cl 2 / 3 XRD patterns of nanomaterials; Figure 2 The Fe3O4 / BiOI 1 / 3 Cl 2 / 3 SEM and EDS images; Figure 3 The Fe3O4 / BiOI 1 / 3 Cl 2 / 3 XPS graph of Figure 4 The Fe3O4 / BiOI 1 / 3 Cl 2 / 3 , nitrogen adsorption-desorption isotherms and pore size distribution of Fe3O4 / BiOCl; Figure 5 The composite material Fe3O4 / BiOI of the present invention 1 / 3 Cl 2 / 3 Magnetic hysteresis loop at room temperature (300K); Figure 6 The Fe3O4 / BiOCl and BiOI 1 / 3 Cl 2 / 3 and Fe3O4 / BiOI 1 / 3 Cl 2 / 3 UV-Vis diffuse reflectance spectrum and (αhν) 1 / 2 A graph showing the relationship between the energy of a photon and the energy of a photon; Figure 7 This is a diagram of the photocatalytic degradation of TC ([TC] = 10 mg / L, [catalyst] = 0.6 g / L) under simulated visible light illumination conditions of the present invention; Figure 8 The Fe3O4 / BiOI x Cl y Catalytic degradation of TC (x / y = 1:1, 1:2; 1:3, 1:4, 1:5) ([TC] = 10 mg / L, [catalyst] = 0.6 g / L) diagram; Fig. 9 The Fe3O4 / BiOI1 / 3 Cl 2 / 3 Experimental diagram of recycling of TC degraded from composite materials; Fig.10 The molecular structure of TC in the present invention and the molecular form of TC under different pKa values, Fe3O4 / BiOI in the range of pH2-10 1 / 3 Cl 2 / 3 Zeta potential, the relationship between the apparent first-order reaction rate constant K of TC degradation and pH, and the relationship between TC adsorption and pH; Fig.11 This is a mechanism diagram of the present invention simulating the photocatalytic degradation of TC by Fe3O4 / BiOI1 / 3Cl2 / 3 under visible light; DETAILED DESCRIPTION

[0019] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the embodiments of the present invention, and should not be construed as limiting the present invention. Example 1

[0020] This embodiment discloses a magnetic Fe3O4 composite bismuth oxyhalide photocatalytic material and a preparation method thereof, comprising the following steps: S1. In a 250 mL three-necked flask, add 10 mmol of bismuth nitrate pentahydrate and 20 mL of 4 mol / L nitric acid respectively and mix; S2, after the bismuth nitrate is dissolved, add 1.660 g potassium iodide, 0.585 g sodium chloride and 40 mmol sodium dodecyl sulfate, and then add 58 mg nano-sized Fe3O4; S3. Place a 250 mL three-necked flask in a constant temperature water bath at 85°C. After mechanical stirring at 700 rpm for 10 min, slowly drop 20 mL of ammonia water and 40 mL of deionized water into the three-necked flask. A light yellow or orange precipitate will gradually appear in the flask (different iodine and chlorine ratios result in different colors). After the dropwise addition, continue stirring the mixture at 700 rpm and react at 85°C for 4 h.

[0021] S4. After the reaction is completed, the three-necked bottle is cooled naturally to room temperature. The supernatant in the bottle is removed by magnetic separation, and the obtained precipitate is washed three times with deionized water and ethanol respectively, and then placed in an oven to dry at 60°C to obtain Fe3O4 / BiOI x Cl yBinary composite visible light catalyst, the mass of NaCl can be adjusted during the experiment to obtain photocatalysts with different molar ratios of iodine and chlorine (e.g. 1:1, 1:2, 1:3, 1:4, 1:5). Example 2

[0022] This embodiment discloses a magnetic Fe3O4 composite bismuth oxyhalide photocatalytic material and a preparation method thereof, comprising the following steps: S1. In a 250 mL three-necked flask, add 12 mmol of bismuth nitrate pentahydrate and 22 mL of 6 mol / L nitric acid respectively and mix; S2, after the bismuth nitrate is dissolved, add 1.760 g potassium iodide, 2.925 g sodium chloride and 42 mmol sodium dodecyl sulfate, and then add 58 mg nano-sized Fe3O4; S3. Place a 250 mL three-necked flask in a constant temperature water bath at 87°C. After mechanical stirring at 700 rpm for 12 min, slowly drop 22 mL of ammonia water and 42 mL of deionized water into the three-necked flask. A light yellow or orange precipitate gradually appears in the flask (different colors depend on different iodine-chlorine ratios). After the dropwise addition, continue stirring the mixture at 700 rpm and react at 85°C for 4 h.

[0023] S4. After the reaction is completed, the three-necked bottle is cooled naturally to room temperature. The supernatant in the bottle is removed by magnetic separation, and the obtained precipitate is washed three times with deionized water and ethanol respectively, and then placed in an oven to dry at 60°C to obtain Fe3O4 / BiOI x Cl y Binary composite visible light catalyst, the mass of NaCl can be adjusted during the experiment to obtain photocatalysts with different molar ratios of iodine and chlorine (e.g. 1:1, 1:2, 1:3, 1:4, 1:5).

[0024] Experimental test analysis Conduct material characterization analysis Fe3O4 / BiOI 1 / 3 Cl 2 / 3 Phase analysis Figure 1 Fe3O4 / BiOI 1 / 3 Cl 2 / 3 XRD spectrum of composite photocatalyst. Through JADE analysis software, the diffraction peaks of the XRD spectrum at 2θ of 10-80° can match the diffraction peaks unique to the tetragonal phase of BiOCl, and the corresponding standard card is JCPDS NO.06-0249. The complete characteristic diffraction peaks of BiOI are not obvious, and some characteristic peaks are Figure 1There is no obvious diffraction peak of Fe3O4 in the figure, because its content is small and the diffraction intensity is much lower than that of bismuth oxyhalide. The XRD diffraction pattern shows that BiOCl and BiOI coexist in Fe3O4 / BiOI 1 / 3 Cl 2 / 3 In addition, there are no other impurity peaks in the sample, indicating that the prepared catalyst has high crystallinity and purity.

[0025] Fe3O4 / BiOI 1 / 3 Cl 2 / 3 Morphological analysis The scanning electron microscope images can provide an intuitive understanding of Fe3O4 / BiOI 1 / 3 Cl 2 / 3 microscopic form. Figure 2 (a) and (b) are composite photocatalysts Fe3O4 / BiOI obtained at different magnifications. 1 / 3 Cl 2 / 3 The SEM images are at magnifications of 10,000 KX and 20,000 KX. 1 / 3 Cl 2 / 3 The composite material contains a large number of sheet-like structures. These nanosheets are crisscrossed and overlapped with each other. After self-assembly, the overall structure presents a flower-like microsphere structure. Figure 2 (c) Composite photocatalyst Fe3O4 / BiOI 1 / 3 Cl 2 / 3 EDS graph of . Blue, green, red, purple and yellow represent elements such as O, I, Fe, Bi and Cl respectively. Figure 2 (d) is their relative response intensity. The above results show that the catalyst is composed of Fe, O, Bi, I and Cl elements; that is, iodine element has been loaded into Fe3O4 / BiOCl.

[0026] Fe3O4 / BiOI 1 / 3 Cl 2 / 3 XPS spectrum analysis In order to further verify the chemical composition of the composite material and analyze the Fe3O4 / BiOI 1 / 3 Cl 2 / 3 The chemical state of the elements in the microspheres was characterized by XPS, and the results are as follows Figure 3 As shown. Figure 3(a) The XPS spectrum of the sample shows the absorption peaks corresponding to the binding energies of Bi 4f, Bi5d, Cl 2p, I 3d, C 1s, O 1s and Fe 2p. In addition, the test results show that the iodine-chlorine ratio of the sample is consistent with the ratio of iodine-chlorine dosage during synthesis, both of which are 1:2. In the peak separation process, the binding energies corresponding to all elements are calibrated with the binding energy corresponding to C 1s, 284.6 eV. Figure 3 (b) is the spectrum of Bi 4f. 7 / 2 and Bi 4f 5 / 2 The binding energies of Bi in BiOX (X = Cl, I) are 159.0 eV and 164.3 eV, respectively. 3+ In the Cl2p spectrum, two well-resolved peaks at 197.8 eV and 199.3 eV can be observed, which is consistent with the Cl - The characteristics are consistent. Figure 3 (d) is the high-resolution spectrum of O 1s. The peak of O 1s at 531.1 eV is attributed to [Bi2O2] inside BiOX. 2+ The second peak at 530.0 eV is attributed to the Bi-O bond in the layer, and the second peak at 530.0 eV is attributed to the Fe-O bond. Figure 3 In (e), I 3d was observed at binding energies of 619.1 eV and 530.5 eV. 5 / 2 and I 3d 3 / 2 The characteristic peaks of the composite photocatalyst indicate that the state of I in the composite photocatalyst is -1. Due to the very small content of iron, the peaks with sufficient intensity are not presented under the interference of noise. In summary, the results prove that the composite photocatalyst is composed of Fe, O, Bi, I and Cl, which is consistent with the conclusion of EDS mentioned above.

[0027] Fe3O4 / BiOI 1 / 3 Cl 2 / 3 BET surface area analysis and pore size distribution Figure 4 (a) Photocatalyst Fe3O4 / BiOI 1 / 3 Cl 2 / 3 The nitrogen adsorption-desorption curve belongs to the IV type adsorption isotherm with H3 type hysteresis loop. Figure 4 (c) is the photocatalyst Fe3O4 / BiOI 1 / 3 Cl 2 / 3 The pore size distribution diagram of the composite photocatalyst Fe3O4 / BiOI synthesized in this study was calculated using the Barrett-Joyner-Halenda model and found that the pore size was concentrated in the range of 2 nm-20 nm. 1 / 3 Cl2 / 3 It is a mesoporous material. Fe3O4 / BiOI 1 / 3 Cl 2 / 3 The BET specific surface areas and other structural parameters of Fe3O4 / BiOCl are listed in Table 1. Figure 4 (b) is the nitrogen adsorption-desorption curve of the photocatalyst Fe3O4 / BiOCl. Figure 4 (d) is the pore size distribution of Fe3O4 / BiOCl. Compared with Fe3O4 / BiOCl sample, Fe3O4 / BiOI 1 / 3 Cl 2 / 3 The catalyst exhibits a large BET surface area, average pore diameter D and pore volume. Fe3O4 / BiOI 1 / 3 Cl 2 / 3 The high specific surface area can promote the adsorption and diffusion of pollutant molecules, and the relatively large pore volume is conducive to the light entering the deeper space inside the catalyst, which is beneficial for the catalyst to capture light quanta. Such a mesoporous structure is equivalent to providing more active sites, which is conducive to the photocatalytic degradation of target pollutant molecules. This speculation is in the subsequent Fe3O4 / BiOI 1 / 3 Cl 2 / 3 The photocatalytic degradation of TC was verified in the experiment.

[0028] Table 1. Fe3O4 / BiOI 1 / 3 Cl 2 / 3 and adsorption parameters of Fe3O4 / BiOCl

[0029] Fe3O4 / BiOI 1 / 3 Cl 2 / 3 Magnetic analysis Figure 5 Composite photocatalyst Fe3O4 / BiOI 1 / 3 Cl 2 / 3 Magnetic hysteresis loop at 300K. From the curve in the figure, it can be seen that the catalyst has superparamagnetism, the same as pure Fe3O4 and Fe3O4 / BiOCl. The magnetic saturation intensity of pure Fe3O4 is 17.5 emu / g, the magnetic saturation intensity of Fe3O4 / BiOCl is 2.50 emu / g, and the composite photocatalyst Fe3O4 / BiOI 1 / 3 Cl 2 / 3 The magnetic saturation intensity of Fe3O4 / BiOI is 2.25 emu / g. 1 / 3 Cl 2 / 3 The magnetization intensity of Fe3O4 / BiOI is relatively low, but from the following 1 / 3 Cl 2 / 3Recycling experiments have shown that the material still has good recycling performance. Under the action of an external magnetic field, the photocatalyst can still be quickly and efficiently separated from the reaction solution, and has good application potential.

[0030] Fe3O4 / BiOI 1 / 3 Cl 2 / 3的 UV-Vis diffuse reflectance spectroscopy test and energy band determination Fe3O4 / BiOCl、BiOI 1 / 3 Cl 2 / 3 and Fe3O4 / BiOI 1 / 3 Cl 2 / 3 The UV-Vis diffuse reflectance spectrum test results are as follows Figure 6 (a) As shown in Figure 2, for Fe3O4 / BiOCl, the maximum light absorption wavelength is 390 nm. After adding iodine during the synthesis process, the catalyst Fe3O4 / BiOCl was obtained. 1 / 3 Cl 2 / 3 , its light absorption wavelength undergoes a significant red shift, and the response wavelength range extends to the visible light region (400 nm - 600 nm). Figure 6 (b) (αhν) 1 / 2 The relationship curve between Fe3O4 / BiOCl and photon energy shows that the band gap energy of Fe3O4 / BiOCl is 3.30 eV, and that of Fe3O4 / BiOI 1 / 3 Cl 2 / 3 The band gap energy of BiOI is 1.70 eV. 1 / 3Cl 2 / 3 The band gap energy of the photocatalyst is 1.80 eV. This result shows that the addition of iodine greatly reduces the band gap energy of the photocatalyst. 1 / 3 Cl 2 / 3 Under visible light irradiation conditions, it can be excited to produce holes and electrons, which then attack pollutant molecules.

[0031] Fe3O4 / BiOI 1 / 3 Cl 2 / 3 Photocatalytic performance Catalyst Fe3O4 / BiOI 1 / 3 Cl 2 / 3 Application of visible light in TC degradation A 500 W xenon lamp and a 420 nm filter were used as cutoff to simulate visible light illumination. The Fe3O4 / BiOI composite material was tested by detecting the concentration change of tetracycline (TC) solution with an initial concentration of 10 mg / L over the illumination time. 1 / 3Cl 2 / 3 The photocatalytic performance of Figure 7As shown. Under simulated visible light conditions, after 60 min of illumination, the photocatalyst Fe3O4 / BiOI 1 / 3 Cl 2 / 3 The removal rate of TC is 100%. Under the same other conditions, the photocatalyst Fe3O4 / BiOCl is used to degrade TC. From the experimental results, it can be seen that the removal rate is only 20%. It is not difficult to infer that with the addition of iodine, on the one hand, the composite material Fe3O4 / BiOCl 1 / 3 Cl 2 / 3 The absorption wavelength of light is broadened to the visible light region, but the composite material Fe3O4 / BiOCl has almost no absorption in the visible light region; on the other hand, Fe3O4 / BiOI 1 / 3 Cl 2 / 3 The band gap energy of Fe3O4 / BiOCl is 1.70 eV, and the band gap energy of Fe3O4 / BiOCl is 3.30 eV. Therefore, under visible light irradiation, the high responsivity and relatively low band gap energy make Fe3O4 / BiOI 1 / 3 Cl 2 / 3 It is easier to be stimulated by visible light to produce a series of subsequent reactions, showing the characteristics of energy saving and high efficiency. In addition, compared with Fe3O4 / BiOCl, Fe3O4 / BiOI 1 / 3 Cl 2 / 3 It has a larger specific surface area and pore volume, so it can show better adsorption in the reaction, increasing the contact efficiency between the catalyst and the pollutant molecules, which is also the reason for highlighting the efficient photocatalytic performance.

[0032] I / Cl molar ratio of catalyst Although the addition of iodine is beneficial to broaden the light absorption range, it will also affect the redox ability of photogenerated holes and electrons to a certain extent, thereby affecting the photocatalytic degradation effect. In order to optimize the photocatalyst, five photocatalysts were prepared by changing the I / Cl molar ratio (I / Cl = 1:1, 1:2, 1:3, 1:4, 1:5) during the preparation process. Their photocatalytic degradation results for TC are shown in Figure 8 The results show that after 60 min of irradiation under simulated visible light conditions, the removal rate increases as the I / Cl molar ratio decreases from 1:1 to 1:2, while the continuous decrease in the I / Cl molar ratio inhibits the degradation rate. When the molar ratio of I to Cl is 1:2, the highest removal rate is 92.3%. That is, among the five catalysts, Fe3O4 / BiOI 1 / 3 Cl 2 / 3 Best.

[0033] Fe3O4 / BiOI 1 / 3 Cl 2 / 3 Recycling Investigation of Fe3O4 / BiOI by recycling experiment1 / 3 Cl 2 / 3 Stability of photocatalyst. Composite photocatalyst Fe3O4 / BiOI 1 / 3 Cl 2 / 3 The reuse of the product is achieved by applying an external magnetic field. The effect of magnetic separation and photodegradation is as follows: Fig. 9 Composite material Fe3O4 / BiOI 1 / 3 Cl 2 / 3 After two cycles, the removal rate of tetracycline dropped from 100% to about 80%, showing a slight deactivation feature. On the one hand, this may be due to a certain amount of catalyst loss after washing with water and ethanol during the recovery process. On the other hand, since the reaction is an interfacial reaction, some difficult-to-degrade intermediates may be deposited on the catalyst surface after two consecutive cycles, resulting in a decrease in the adsorption capacity for TC molecules, reducing the contact opportunity between active species and TC molecules, and thus reducing the degradation efficiency. However, when it was used for the third time, the removal rate was still maintained at 80%, indicating that Fe3O4 / BiOI 1 / 3 Cl 2 / 3 It still has certain practical application potential.

[0034] Effect of pH Fig.10 (a) shows the molecular structure and physicochemical parameters of TC. TC has three pKa values, 3.32, 7.78 and 9.58. When the pH in the system is less than pKa1 (3.32), the TC molecule is positively charged; when the pH is greater than pKa1 (3.32) and less than pKa2 (7.78), the TC molecule is neutral; when the pH is greater than pKa3 (9.58), the TC molecule is negatively charged. Fig.10 (b) Fe3O4 / BiOI 1 / 3 Cl 2 / 3 The pH-Zeta potential diagram shows that the isoelectric point is 4.6. Therefore, the composite catalyst Fe3O4 / BiOI 1 / 3 Cl 2 / 3 In the pH range of 4.6-10.0, its surface is negatively charged, and the higher the pH, the more negative charge it carries. Fig.10 (c) is the apparent first-order reaction rate constant (k)-pH diagram of TC photodegradation. It is not difficult to see that the pH in the system strongly affects the photocatalytic degradation efficiency of TC. When the pH value of the system is in the range of 1-7, the photocatalytic degradation efficiency is almost proportional to the pH and reaches the maximum value at pH = 7; then when the pH value of the TC solution increases from 7 to 10, the photocatalytic efficiency decreases. The trend of TC degradation efficiency with pH is related to the adsorption amount of TC ( Fig.10(d)) has a similar trend with pH, ​​so the adsorption relationship between the catalyst and TC may be the key factor leading to the difference in degradation efficiency, and electrostatic repulsion and complexation may be the two key factors affecting adsorption performance. Under acidic conditions (pH 2-4.6), the catalyst Fe3O4 / BiOI 1 / 3 Cl 2 / 3 The surface of Fe3O4 / BiOI is positively charged, while TC is almost in cationic form at low pH (pH < 4.6). There is a strong electrostatic repulsion between the two, which inhibits the adsorption of TC by the catalyst and leads to low photocatalytic efficiency. Under neutral or near-neutral conditions (pH 5-7), the catalyst Fe3O4 / BiOI 1 / 3 Cl 2 / 3 Negatively charged, TC exists in the form of zwitterions, and appears neutral and uncharged. Although there is no electrostatic repulsion or attraction between the catalyst and TC, TC may combine with Bi through the oxygen atom in the enol hydroxyl group on the carbon atom No. 3 and the nitrogen atom in the dimethylamino group on the carbon atom No. 2, thereby promoting the catalyst to adsorb TC and thus improve the degradation efficiency. Under alkaline conditions (pH 7-10), TC is in the form of anions, and the catalyst Fe3O4 / BiOI 1 / 3 Cl 2 / 3 It is negatively charged and the negative charge increases with the increase of pH. Then the electrostatic repulsion between the catalyst and TC also increases, inhibiting the adsorption. At the same time, as the pH increases, the hydroxyl group on the 10th or 12th carbon atom and the carbonyl group on the 11th carbon atom can be complexed with Bi, that is, the number of sites in the TC molecule that can be complexed with Bi increases, and one TC molecule will bind three Bi atoms. From the side, the amount of TC adsorbed by the catalyst will decrease. Therefore, under alkaline conditions, the degradation efficiency will be negatively correlated with the pH value.

[0035] Photocatalyst Fe3O4 / BiOI 1 / 3 Cl 2 / 3 Degradation mechanism Fe3O4 / BiOI 1 / 3 Cl 2 / 3The photocatalytic degradation process of TC includes two processes: adsorption and interfacial reaction. From the experiment of identifying TC intermediates using LC-TOF MS, the same products were detected in the catalyst surface eluent and the liquid phase medium of the solution. Therefore, it is speculated that the photodegradation reaction of TC occurs both on the catalyst surface and in the solution. The specific positions of the conduction band and valence band of the semiconductor photocatalyst are calculated using the formula: EVB = X-Ee+ 0.5Eg and the formula: ECB = EVB–Eg. Among them, EVB and ECB represent the potentials of the valence band (VB) and conduction band (CB), respectively, X is the electronegativity of the semiconductor, the X value of BiOI is 5.99 eV, Ee is the energy hydrogen scale of free electrons (approximately 4.5 eV), and Eg is the band gap energy of the semiconductor. It can be calculated that BiOI 1 / 3 Cl 2 / 3 The EVB and ECB of semiconductor photocatalysts are 2.39 eV and 0.59 eV, respectively. + and e - The transfer mechanism is shown in Fig.11 However, due to the photocatalyst Fe3O4 / BiOI 1 / 3 Cl 2 / 3 The addition of iodine to the BiOI increases the spectral range. Under visible light irradiation, the minimum wavelength of 420 nm shows maximum absorption, which corresponds to a maximum energy of 2.95 eV. 1 / 3 Cl 2 / 3 The band gap energy of BiOI is 1.80 eV, so 1 / 3 Cl 2 / 3 The photogenerated electrons can be excited to a higher potential edge, that is, the potential can be from 0.59 eV to -0.56 eV. Similarly, Fe3O4 may also form a new conduction band potential (-2.68 eV). 1 / 3 Cl 2 / 3 The potential difference between the valence band and the conduction band, the photogenerated h + and e - will transfer, and finally make e - Aggregate to BiOI 1 / 3 Cl 2 / 3 The conduction band of h + The photogenerated electrons and holes of the composite photocatalyst are effectively separated. 1 / 3 Cl 2 / 3 e on the conduction band - Redox potential ratio O2 / O2• -(Ψ=-0.046 eV) is low, then O2 adsorbed on the surface of the photocatalyst can oxidize e- to produce O2• - . Fe3O4 valence band h + The redox potential is lower than that of H2O / HO• (2.3 eV) and HO• / OH- (2.38 eV), then h + Cannot oxidize H2O or OH - HO• hydroxyl radicals are produced. Therefore, in Fe3O4 / BiOI 1 / 3 Cl 2 / 3 In the system of photocatalytic degradation of TC, the main active species is h + and O2• - In order to confirm the above speculation, free radical capture experiments were carried out. Ammonium oxalate and isopropanol were added to the system as h + and HO• scavenger. Continuous nitrogen bubbling into the reaction system ensures nitrogen saturation to eliminate superoxide radicals (O2• - ) is formed. The experimental results are listed in Table 2. It can be inferred that in Fe3O4 / BiOI 1 / 3 Cl 2 / 3 In the system, h + , HO• and O2• − The contributions of are 85.34%, 0.66% and 8.59% respectively, which is consistent with the above inference.

[0036] Table 2 Contribution of each active species to TC degradation

[0037] In summary, in this study, iodine was loaded onto magnetic bismuth oxychloride nanomaterials by coprecipitation to successfully prepare the composite photocatalyst Fe3O4 / BiOI. 1 / 3 Cl 2 / 3 . The purpose of visible light driven photocatalysis and energy saving is achieved. The photocatalytic performance of TC was studied by using this material under simulated visible light irradiation conditions to explore the photocatalytic mechanism, investigate the influencing factors such as pH, and speculate on the possible reaction path. The specific conclusions are as follows: (1) Fe3O4 / BiOI was successfully prepared using a simple method 1 / 3 Cl 2 / 3 The catalyst presents a flower-like microsphere structure and has a larger specific surface area than Fe3O4 / BiOCl.

[0038] (2) Composite photocatalyst Fe3O4 / BiOI 1 / 3 Cl 2 / 3Visible light response was achieved, and the photocatalytic degradation of TC was excellent under simulated visible light conditions. After 60 min of illumination, the degradation rate of TC could reach up to 100%, and compared with acidic and alkaline conditions, the degradation effect was best under neutral conditions.

[0039] (3) The heterojunction formed by ferroferric oxide and bismuth oxyhalide is a bridge for the transfer of photogenerated holes and electrons. The difference from Fe3O4 / BiOCl catalyst is that in Fe3O4 / BiOI 1 / 3 Cl 2 / 3 In the photocatalytic system, h + and O2• - The reason is that under the irradiation of visible light, BiOI 1 / 3 Cl 2 / 3 The photogenerated electrons can be excited to a higher potential edge when its value is lower than O2 / O2• - (Ψ=-0.046 eV), the photogenerated electrons can be oxidized by oxygen to form O2• - .

[0040] (4) By applying an external magnetic field, Fe3O4 / BiOI 1 / 3 Cl 2 / 3 The catalyst can be easily separated from the reaction solution, and the photocatalytic performance is relatively stable. Compared with Fe3O4 / BiOCl, the composite photocatalyst Fe3O4 / BiOI 1 / 3 Cl 2 / 3 It has a larger specific surface area and pore volume, and exhibits adsorption capacity during the pollutant degradation experiment. The more substances adsorbed, the better the subsequent photolysis effect.

[0041] The embodiments disclosed above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made on the basis and within the scope of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a magnetic Fe3O4 composite bismuth oxyhalide photocatalytic material, characterized in that: The steps include: S1. Mixing bismuth nitrate pentahydrate and nitric acid in a container; S2, after the bismuth nitrate is dissolved, potassium iodide, sodium chloride and sodium dodecyl sulfate are added, and then nano-sized Fe3O4 is added; S3, placing the container in a constant temperature water bath and stirring, adding ammonia water and deionized water after stirring to obtain a mixture, and gradually showing a light yellow or orange precipitate in the bottle, stirring the mixture and reacting; S4. After the reaction is completed, the mixture is cooled to room temperature, the supernatant in the container is removed by magnetic separation, and a precipitate is obtained. The precipitate is washed and dried to obtain Fe3O4 / BiOI x Cl y Binary composite visible light photocatalyst.

2. The method for preparing the magnetic Fe3O4 composite bismuth oxyhalide photocatalytic material according to claim 1, characterized in that: The molar mass of the bismuth nitrate pentahydrate is 10 mmol to 12 mmol.

3. The method for preparing the magnetic Fe3O4 composite bismuth oxyhalide photocatalytic material according to claim 1, characterized in that: The concentration of the nitric acid is 4 mol / L to 6 mol / L, and the volume is 20 mL to 22 mL.

4. The method for preparing the magnetic Fe3O4 composite bismuth oxyhalide photocatalytic material according to claim 1, characterized in that: The mass of the potassium iodide is 1.660 g to 1.760 g, the mass of the sodium chloride is 0.585 g to 2.925 g, and the molar mass of the sodium dodecyl sulfate is 40 mmol to 42 mmol.

5. The method for preparing the magnetic Fe3O4 composite bismuth oxyhalide photocatalytic material according to claim 1, characterized in that: The temperature of the constant temperature water bath is 85°C to 87°C, and the stirring time is 10min to 12min.

6. The method for preparing the magnetic Fe3O4 composite bismuth oxyhalide photocatalytic material according to claim 1, characterized in that: The volume of the ammonia water is 20 mL to 22 mL, and the volume of the deionized water is 40 mL to 42 mL.

7. The method for preparing the magnetic Fe3O4 composite bismuth oxyhalide photocatalytic material according to claim 1, characterized in that: The precipitate was washed with deionized water and ethanol multiple times.

8. The method for preparing the magnetic Fe3O4 composite bismuth oxyhalide photocatalytic material according to claim 1, characterized in that: Fe3O4 / BiOI x Cl y The molar ratio of iodine to chlorine in the binary composite visible light catalyst is 1:1-5.

9. A magnetic Fe3O4 composite bismuth oxyhalide photocatalytic material prepared by the preparation method as claimed in any one of claims 1 to 8.

10. Use of the magnetic Fe3O4 composite bismuth oxyhalide photocatalytic material as claimed in claim 9 in TC degradation.

Citation Information

Patent Citations

  • A BiOCl&lt;x&gt;I&lt;y&gt; composite photocatalyst and a preparing method thereof

    CN104307540A

  • Magnetically responsive core-shell photocatalytic material for water purification and preparation method thereof

    CN109201091A

  • BiOBrxI1-x / cellulose composite photocatalytic material, and preparation method and application thereof

    CN109647512A

  • Method for preparing magnetic bismuth oxyhalide photocatalyst and application

    CN116920889A